Perancangan Buku Panduan Optimalisasi Sosial Media Instagram Design untuk Meningkatkan Online Engagement - bintang pramudya putra; Aditya Nirwana (Jurnal SASAK : Desain Visual dan Komunikasi, 2023)
The development of social media has become a new axis in the process of marketing a product to the public, the ability of social media to gather millions of users attracts the attention of business people to do marketing for their products more easily, quickly and cheaply compared to conventional marketing media such as placing billboards or do television advertisements. Even though social media offers various conveniences for doing business, there are still many small business actors who have not used social media or have difficulty using it to promote their products, the unfamiliarity of using technology is a big obstacle for those who are not used to it. The design thinking method is used to really understand the problems in the field and plan solutions based on the most appropriate and easy to understand approach. The existence of a template that can be directly used by business actors encourages the desire to start carrying out promotions to increase their sales, even though using templates makes it easier for business actors to promote, more alternative templates is needed to avoid the potential for design similarities during promotions.